Item local independence in WACE (SSCE) economics in Ajeromi-Ifelodun local government area, Lagos state (2011)
The differential scholastic achievement of students' assessment by examining bodies seems to be the "Holy Grail" in the education reform. If Nigeria would be among the 20 best economies, compaarative standards must be maintained in our education sector before actualizing this dream. With an eye towards research and practice, this study reviewed and evaluated main trends that have contributed to the increasing use of assessment mechanisms to assess and evaluate students'. The goal of this paper was to highlight the major issues and challenges of massive failures recorded by examining bodies using of Item Response Thoery(IRT) assumptions, which is local independence. The study adopted a survey research design and simple random sampling techniques was used to select 750 students that were preparing for the 2012 WACE (SSCE) Economics examination in LAgos state. Two research questions were addresses using descriptive staistics, TSP, TID and Tetrachoric correlation to locate the extent at which WAEC items are locally independent. Findings from this study revealed that a larger percentage of the students' proficiency level on the test-item cut across different ability group, while the tetrachoric correlation revealed that WAEC (SSCE) economics objective items for 2010 met the assumptions of IRT on local Independence. Thus, it is recommended that examing bodies, evaluators, assessors, tertiary institutions, parents and government should welcome the use of IRT in our educational system for quality assessments procedure,while measurement and evaluation courses need to be reviewed to inculcate more practical work than theory-based.